Partial diazoxide responsiveness in a neonate with hyperinsulinism due to homozygous ABCC8 mutation. (11th February 2019) - Kiff, Sarah; Babb, Carolyn; Guemes, Maria; Dastamani, Antonia; Gilbert, Clare; Flanagan, Sarah E; Ellard, Sian; Barton, John; Dattani, M; Shah, Pratik
Summary: We report a case of partial diazoxide responsiveness in a child with severe congenital hyperinsulinaemic hypoglycaemia (CHI) due to a homozygous ABCC8 mutation. A term baby, with birth weight 3.8 kg, born to consanguineous parents presented on day 1 of life with hypoglycaemia. Hypoglycaemia screen confirmed CHI. Diazoxide was commenced on day 7 due to ongoing elevated glucose requirements (15 mg/kg/min), but despite escalation to a maximum dose (15 mg/kg/day), intravenous (i.v.) glucose requirement remained high (13 mg/kg/min). Genetic testing demonstrated a homozygous ABCC8 splicing mutation (c.2041-1G>C), consistent with a diffuse form of CHI. Diazoxide treatment was therefore stopped and subcutaneous (s.c.) octreotide infusion commenced. Despite this, s.c. glucagon and i.v. glucose were required to prevent hypoglycaemia. A trial of sirolimus and near-total pancreatectomy were considered, however due to the significant morbidity potentially associated with these, a further trial of diazoxide was commenced at 1.5 months of age. At a dose of 10 mg/kg/day of diazoxide and 40 µg/kg/day of octreotide, both i.v. glucose and s.c. glucagon were stopped as normoglycaemia was achieved. CHI due to homozygous ABCC8 mutation poses management difficulties if the somatostatin analogue octreotide is insufficient to prevent hypoglycaemia. Diazoxide unresponsiveness is often thought to be a hallmark of recessively inherited ABCC8 mutations. This patient was initially thought to be non-responsive, but this case highlights that a further trial of diazoxide is warranted, where other available treatments are associated with significant risk of morbidity. Learning points: Homozygous ABCC8 mutations are commonly thought to cause diazoxide non-responsive hyperinsulinaemic hypoglycaemia. This case highlights that partial diazoxide responsiveness in homozygous ABCC8 mutations may be present. Trial of diazoxide treatment in combination with octreotide is warranted prior to considering alternative treatments, such as sirolimus or near-total pancreatectomy, which are associated with more significant side effects.